Meningococcal serogroup W135 epiglottitis in an adolescent patient. (5th March 2018) - Beltrami, Daniela; Guilcher, Pierre; Longchamp, David; Crisinel, Pierre Alex
Abstract : Acute epiglottitis is a severe and potentially life-threatening condition. Since the implementation of Haemophilus influenzae vaccination, the number of cases of epiglottitis has decreased and the proportion of other infectious causes has increased. We report a case of acute epiglottitis in a teenager caused by Neisseria meningitidis, an unusual pathogen.